2022
DOI: 10.1155/2022/4054938
|View full text |Cite
|
Sign up to set email alerts
|

BMS-470539 Attenuates Oxidative Stress and Neuronal Apoptosis via MC1R/cAMP/PKA/Nurr1 Signaling Pathway in a Neonatal Hypoxic-Ischemic Rat Model

Abstract: Neuronal apoptosis induced by oxidative stress plays an important role in the pathogenesis and progression of hypoxic-ischemic encephalopathy (HIE). Previous studies reported that activation of melanocortin-1 receptor (MC1R) exerts antioxidative stress, antiapoptotic, and neuroprotective effects in various neurological diseases. However, whether MC1R activation can attenuate oxidative stress and neuronal apoptosis after hypoxic-ischemic- (HI-) induced brain injury remains unknown. Herein, we have investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 71 publications
(126 reference statements)
0
8
0
1
Order By: Relevance
“…17,18 Apart from mediating inflammatory processes through the activation of IL-8 and the suppression of IL-4 in T-reg, 19,20 NR4A2 (encodes the NURR1 protein) also inhibits the transcription of the OS gene. 21,22 Sodium butyrate (NaBu) is a short-chain fatty acid that increases the average daily weight gain of piglets, provides energy for intestinal epithelium, plays an immunomodulatory role, and also regulates lipid metabolism in the liver and intestine. 23 Notably, as a vital ligand of NR and a natural HDAC inhibitor, NaBu could alleviate DON- induced OS and inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Apart from mediating inflammatory processes through the activation of IL-8 and the suppression of IL-4 in T-reg, 19,20 NR4A2 (encodes the NURR1 protein) also inhibits the transcription of the OS gene. 21,22 Sodium butyrate (NaBu) is a short-chain fatty acid that increases the average daily weight gain of piglets, provides energy for intestinal epithelium, plays an immunomodulatory role, and also regulates lipid metabolism in the liver and intestine. 23 Notably, as a vital ligand of NR and a natural HDAC inhibitor, NaBu could alleviate DON- induced OS and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Mycotoxin is tightly linked with the transcriptional processes involved in NR-mediated regulation . Increasing evidence have shown that NRs exert cardinal roles in regulating DON-induced OS and inflammatory genes through the recruitment of histone modifiers. , Apart from mediating inflammatory processes through the activation of IL-8 and the suppression of IL-4 in T-reg, , NR4A2 (encodes the NURR1 protein) also inhibits the transcription of the OS gene. , Sodium butyrate (NaBu) is a short-chain fatty acid that increases the average daily weight gain of piglets, provides energy for intestinal epithelium, plays an immunomodulatory role, and also regulates lipid metabolism in the liver and intestine . Notably, as a vital ligand of NR and a natural HDAC inhibitor, NaBu could alleviate DON-induced OS and inflammation. , Moreover, NaBu exerts anti-inflammatory effects by increasing the H3K9ac profiles at promoter regions of the pro-inflammatory genes and enhancing NR PPARA activation. Therefore, we hypothesize NaBu resists DON-induced OS and the inflammatory response through histone acetylation recruited by NR4A2 .…”
Section: Introductionmentioning
confidence: 99%
“…KEGG analysis showed significant enrichment of differentially expressed circRNAs in pathways related to neuronal injury, such as the "MAPK signaling pathway" and "cAMP signaling pathway". For example, previous evidence has shown that the MAPK signaling pathway plays a vital role in spinal cord injury and ischemic stroke (Tian et al, 2020;Zhang et al, 2021), while the cAMP signaling pathway is a critical regulator of neuronal apoptosis (Liu et al, 2020;Yu et al, 2022). Besides that, functional annotation also showed that the top five differentially expressed circRNAs were enriched in distinct GO and KEGG pathways, demonstrating Frontiers in Genetics frontiersin.org important roles of these circRNAs may play in LSRA.…”
Section: Discussionmentioning
confidence: 89%
“…Reference to previous methods, hematoxylin and eosin (HE) were used to stain the colon and kidney tissues [ 16 ]. The inflammation of colon tissue was evaluated according to the degree of infiltration of inflammatory cells.…”
Section: Methodsmentioning
confidence: 99%